Akta SB nie kłamią, ale mogą wprowadzić w błąd. Z badań nad dokumentami dotyczącymi osobowych żródeł informacji SB - Bereszyński, Zbigniew (Pamięć i Sprawiedliwość, 2012)
The materials created by the Security Service (SB, Służba Bezpieczeństwa) of the Ministry of Interior (MI) and other special services of the People’s Republic of Poland (PRL, Polska Rzeczpospolita Ludowa) are valuable, and often even irreplaceable sources that enable conducting research on the most recent history of Poland. However, they ought to be treated in a reasonable manner, with utmost caution, because they were created by the services that conspired their operational activity also within their own ranks. One ought to remember about the different specifics of the operational materials allocated for internal use by SB operational units, as well as other materials, such as for instance investigative files, personal files of internees, reporting materials, inter-department or external correspondence. This concerns especially the documentation concerning the human intelligence sources of the SB. The persons registered as SB human intelligence sources could be interrogated or searched by officers of the SB investigation division who were not fully familiar with the actual role of the individual. The documentation created on such occasions (interrogation or search protocols, etc.) simply could not contain information that the given individual performed the role of an agent. The same concerns court and prosecution files. Drawing unilateral conclusions only on the basis of such materials, without including relevant operational materials and record entries, could result in the erroneous belief that we are dealing solely with a victim of oppression. Incorrect conclusions can also be drawn if SB inter-department correspondence or routine correspondence with the MI is used unilaterally. Moreover, these materials could not contain information uncovering human intelligence sources. The same regards the files of those interned during martial law. Opposite situations might also take place – the contents of the preserved entries that confirm the registration of an individual as an SB human